China and Africa : A Century of Engagement - Shinn, David Hamilton (Book collections on Project MUSE., 2012)
The recent growth in relations between China and the nations of Africa is one of the most important geopolitical phenomena of our time. China and Africa presents a unique, comprehensive view of this relationship. This monumental study, the first since the 1970s, examines China's ties with all of Africa's 54 countries.